Canning of ampalaya (Momordica Charantia Linn.) - Siongco, Imelda M.
Two additives CaCl2 and CuSO4 were used to prevent occurence of undesirable changes in texture and color of heat processed ampalaya. Methods of adding these additives were studied to find out whether they are more effective as pretreatments or as packing media. An experimental design representing all possible combinations of four levels CaCl2 and four levels of CuSO4 was used to arrive at the most desirable combination of the two additives on the basis of objective and subjective tests. The minimum process of 250°F and 7 minutes established for canned sitao, packed in IF cans was found adequate for ampalaya using the same size of can. The adequacy of adopted process was confirmed on the basis of the following tests: 1) a heat penetration study of the process time and temperature to determine the sterilizing value of the process; 2) microbiological examination of the stored product to verify sufficient processing; 3) physico-chemical and cut-out tests to evaluate the efficiency of other processing conditions such as exhausting and sealing; and 4) sensory evaluation of the canned product to determine the effect of processing on texture, flavor and color qualities of ampalaya. A standardized formulation and process using 0.005 per cent CuSO4 and 0.1 per cent CaCl2 and employing 250°F at 7 minutes were finally arrived at.